The horror of radicalism: Mary Shelley's Frankenstein and Ahmad Saadawi's Frankenstein in Baghdad - Arikan, Seda; Cetin, Gulsum Tugce (Routledge Journals, Taylor & Francis Ltd, 2024)
Radicalism which has been frequently experienced in history continues to threaten the post-millennial era. The horror it arouses has been reflected in literary works and proceeds to be reflected regarding its relation to the concept of monstrosity. As one of the prominent examples of monstrosity, Mary Shelley's Frankenstein; or, the Modern Prometheus (1818) harbours the horrors of radicalism that appeared during the French Revolution. Among many textual adaptations of Mary Shelley's Frankenstein, Ahmad Saadawi, in Frankenstein in Baghdad (2013) - the first Middle Eastern adaptation of the monstrosity with a reference to Shelley's monster - rewrites the horror of radicalism in the aftermath of the US invasion of Iraq. This paper will discuss, from a comparative perspective, how Shelley and Saadawi deal with radicalism as a form of monstrosity. By asserting that both novels are political narratives exposing the horror of radicalism, this article examines the politics of radicalism and monstrosity in the novels. Thus, the focus is on the two novels operating within the discourse of justice that turns into injustice and terror as well as with intentionally created fear that turns into a vicious circle of violence and vengeance.
Keywords: Mary Shelley; Frankenstein; Ahmad Saadawi; Frankenstein in Baghdad; radicalism; horror; monstrosity